2021
DOI: 10.1128/jvi.02087-20
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Consequences of Newcastle Disease Virus W Protein Subcellular Localization in the Nucleus or Mitochondria

Abstract: We previously demonstrated that W proteins from different Newcastle disease virus (NDV) strains localize in either the cytoplasm (e.g., NDV strain SG10) or the nucleus (e.g., NDV strain La Sota). To clarify the mechanism behind these cell localization differences, we overexpressed W protein derived from four different NDV strains or W protein associated with different cellular regions in Vero cells. This revealed that the key region for determining W protein localization is 180–227aa. Further experiments found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 68 publications
1
22
1
1
Order By: Relevance
“…Fully functional RDRP activity also requires N and P proteins [9]. Due to a phenomenon of RNA editing, when the polymerase co-transcriptionally inserts additional nucleotides [10], the P gene in addition to the mRNA coding for P protein is transcribed into two other mRNAs coding for proteins V and W, the antagonists of the anti-viral response and the major determinants of NDV species restriction [11][12][13][14]. The viral polymerase transcribes NDV genes starting from the 3′ end of the genomic RNA so that it starts and stops the transcription of each gene individually.…”
Section: Introductionmentioning
confidence: 99%
“…Fully functional RDRP activity also requires N and P proteins [9]. Due to a phenomenon of RNA editing, when the polymerase co-transcriptionally inserts additional nucleotides [10], the P gene in addition to the mRNA coding for P protein is transcribed into two other mRNAs coding for proteins V and W, the antagonists of the anti-viral response and the major determinants of NDV species restriction [11][12][13][14]. The viral polymerase transcribes NDV genes starting from the 3′ end of the genomic RNA so that it starts and stops the transcription of each gene individually.…”
Section: Introductionmentioning
confidence: 99%
“…After deletion of its NES, the W protein remains in the nucleus and cannot be sent back to the cytoplasm. We also found that the location of the W protein affects virulence [21] .…”
Section: P V and W Proteinmentioning
confidence: 57%
“…The genome comprises six transcriptional units, encoding a nucleocapsid protein (N), a phosphoprotein (P), a matrix protein (M), a fusion protein (F), a hemagglutinin-neuraminidase protein (HN) and a large polymerase protein (L) [ 1 ]. In addition, the RNA of the P gene can be edited to generate the V or W proteins, which are non-structural and generally associated with modulating the avian host’s immune response [ 44 ]. Techniques for generating recombinant NDV constructs are already well established, with protocols following the general steps of: antigenomic plasmid construction, transfection, rescue and amplification [ 45 ].…”
Section: Designing and Generating Recombinant Ndvmentioning
confidence: 99%